(untitled) (Bangladesh Journal of Nuclear Medicine, 2015)
Thyroid disorders are prevalent in women of childbearing age and for this reason commonly present in pregnancy and the puerperium. Chronic autoimmune thyroiditis (AIT) is the most common and extensively studied organ-specific autoimmune disorder and it has important consequences on fertility, the occurrence of pregnancy complications and pregnancy outcome. Across sectional analytical study has been carried out on autoimmune thyroiditisamong the women of child bearing age with suspected thyroid disorders in the Centre for Nuclear Medicine & Ultrasound, Mymensingh during the period of July, 2011 to June, 2012.The objectives of the study were to estimate the prevalence of autoimmune thyroiditis in women of child bearing age and to determine the association of autoimmune thyroiditis with thyroid function and thyroid antibody status. In the present study, 100 women of childbearing age (15-45Yrs) with any sorts of suspected thyroid disorders were included. But already diagnosed all follow up cases were excluded from the study. High Resolution Ultrasonography (HRUS) had been taken as principal modality of diagnosis of autoimmune thyroiditis. T3, T4 and TSH were taken as an important indicator for thyroid function status. Serum TM-Ab (Thyroid Microsomal Antibody) level and serum Tg-Ab (Thyroglobulin Antibody) level were measured to see the thyroid antibody status. In the present study, prevalence of autoimmune thyroiditis among the women of childbearing age with suspected thyroid disorders was found 41%. According to the thyroid function status, 65.85% AIT patients were found in hypothyroid state, 29.27% in subclinical hypothyroid state and rest 4.88% were found in euthyroid state. In consideration of thyroid antibody status, 69.23% AIT patients were positive & 30.77% were negative for thyroid autoantibody. This study revealed that there were significant association of AIT with the biochemical hypothyroid state and positive thyroid antibody status DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22487 Bangladesh J. Nuclear Med. 17(1): 14-24, January 2014